2010
DOI: 10.1007/s11136-010-9824-0
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and changes in generic and weight-specific quality of life in obese adolescents

Abstract: Changes in generic and weight-specific quality of life scores are associated with weight loss. The weight-specific measure is slightly more sensitive to weight changes; however, when controlling for modifiers, the YQOL-W remained significantly associated with weight loss, while the generic QoL measure did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Moreover, little is known about the effects of intensive lifestyle treatment on the different domains of HRQoL [12]. Such knowledge can provide valuable information on the effectiveness of these treatments in children and adolescents with severe obesity [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, little is known about the effects of intensive lifestyle treatment on the different domains of HRQoL [12]. Such knowledge can provide valuable information on the effectiveness of these treatments in children and adolescents with severe obesity [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the PHS measures had not been previously validated for this specific population, they have been used extensively and validated in other studies that have included Latino youth [14,19,25,34-39]. All study materials were designed to be readable and understandable for a 5 th grade level.…”
Section: Research Methods and Procecuresmentioning
confidence: 99%
“…Numerous studies have also examined the association between obesity and various self-reported perceived health status (PHS) measures, including general health [14, 15], body shape satisfaction [16-19], physical function [14], depressive symptoms [16, 20-22], and quality of life [14, 23-25]. A potential mechanism explaining the association between obesity status and depressive symptoms, for example, involves physical health, such that adolescents with a higher body mass index (BMI) report significantly lower levels of general health [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations